Nutrition security: Mass plantation drive for fruit crops - Singh, Sarvpriya; Singh, Nav Prem (Indian Horticulture, 2025)
Growing demand for fresh fruits, driven by changing food habits and awareness of nutritional benefits, can be met through large-scale fruit plantation drives in villages, towns, cities, institutions, parks, and along roads or canals. In urban areas, compact fruit plants are suitable for limited spaces, while rural households can establish fruit nutrition gardens to improve food and nutrition security. These gardens provide year-round, naturally ripened, pesticide-free fruits for family consumption. NGOs, CSR initiatives, and public and private institutions are promoting fruit plantations by distributing saplings, creating green belts, and enhancing nutrition security among low-income and urban populations.